2018
DOI: 10.4314/tjpr.v17i6.15
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of methanol extracts of selected plants on the proliferation of two human melanoma cell lines

Abstract: Purpose: To investigate the in vitro antiproliferative activity of methanol extracts of six plants regardless of their claimed ethnopharmacological application. Methods: Methanol extracts of different parts of Glycyrrhiza glabra L. Licorice), Matricaria chamomilla L. (Chamomile), Salvia triloba L. (Sage), Rheum palmatum L. (Rhubarb), Trigonella foenum-graecum L (Fenugreek) and Sambucus ebulus L. (Dwarf Elder)were prepared. The antiproliferative effects of the extracts weretestedon two skin cancer melanoma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
3
4
0
1
Order By: Relevance
“…Tyrosinase inhibitors have been shown to have antiproliferative effects against melanoma cell lines. The inhibitory effects of the plant extracts discovered in the current study against the melanotic SK-Mel-5 cell line can be attributed, at least partially, to the tyrosinase inhibitory activity, which was consistent with a similar study by Fraihat et al [18].…”
Section: Discussionsupporting
confidence: 93%
“…Tyrosinase inhibitors have been shown to have antiproliferative effects against melanoma cell lines. The inhibitory effects of the plant extracts discovered in the current study against the melanotic SK-Mel-5 cell line can be attributed, at least partially, to the tyrosinase inhibitory activity, which was consistent with a similar study by Fraihat et al [18].…”
Section: Discussionsupporting
confidence: 93%
“…The IC 50 was 785 g/mL against MDA-MB-468 and 921 g/mL against MCF-7 for aerial parts extracts and 1560 g/mL against MCF-7 for root extracts. The methanolic extract of M. chamomilla has been tested by Fraihat et al [166] on two solid human melanocyte tumor cell lines, A375.S2 and WM1361A. In this study, results showed an inhibition only in the proliferation of the melanotic WM1361A cell line (IC 50 = 25.2 g/mL).…”
Section: Antidiabetic Activitymentioning
confidence: 56%
“…The antiproliferative effect of the extract was tested on WM 1361A (high tyrosinase expression) using the MTT test. The results showed that M. chamomilla methanol extract inhibited the proliferation of melanotic WM1361A with an IC50 value of 25.2 g/ml (Fraihat et al, 2018).…”
Section: Passiflora Caerulea (Blue Passion Flower)mentioning
confidence: 98%